Divergence and dialogue: analyzing the linguistic turn of the archive in digital humanities research - Long, Jiaqing; Frings‑Hessami, Viviane; Feng, Huiling (Archival science, 2025)
Over the past two decades, many digital humanities projects have presented themselves as various forms of digital archives, and the term ‘archive’ has been used frequently by many digital humanists, leading to an expanded but also eroded concept of the archive. This phenomenon, described as the linguistic turn of the archive, has sparked intense debates in both the digital humanities and archival science research communities. The conceptual divergence between the concept of the archive in archival science and in digital humanities can lead to misunderstandings and academic exchange gaps on both sides. To bridge this divide, we conducted research by selecting all 58 cases related to archives from the International Digital Humanities Awards (2012–2023). This study draws on the socio-contextual analysis and discourse–historical analysis framework to code and analyze the characteristics of the linguistic turn. By extracting four layers ‘concept-tool-cognition-scenario’ from existing research, we innovatively proposed a framework suitable for analyzing archival terminologies within the contexts of different projects. Through analysis, we identified the following four turning features: (a) an expansion of the traditional archival terminology, i.e., many digital resources are referred to as ‘digital archive’; (b) the application of archival theories, principles, and tools for resource preservation; (c) the embedding of archival cognition in the processes of digital humanities projects; and (d) the integration of archives into broader and more socially oriented digital scenarios. This paper suggests that archivists and digital humanities researchers need to increase the dialogue between the two disciplines to better facilitate an archival paradigm shift and ensure the sustainability of digital humanities research.